THE EFFECT OF BRAND IMAGE, SERVICE FEATURES, AND PROMOTION ON PURCHASE DECISIONS AT SHOPEE MARKETPLACE (Case Study On Unisla Students) - Niswatun Khasanah; Ratna Handayati; Sutinem Sutinem (Sean Institute, 2022)
The development of technology and information is currently growing very rapidly, making business competition fierce, companies are required to be more creative and must have advantages compared to other companies. This study aims to determine the effect of brand image, service features and promotions partially and simultaneously on purchasing decisions at the shopee marketplace and to determine which variable has the most dominant influence on purchasing decisions at the shopee marketplace. The type of research used is quantitative research. The sampling technique used was purposive sampling. The population in this study were Unisla students with a sample of 98 respondents. The analytical tools used in this research are validity test, reliability test, classical assumption test, multiple correlation, coefficient of determination, multiple linear regression test, t test, and F test. The results of multiple linear regression analysis Y = 1.688 + 0.792 X 1 + 0.176 X 2 + 0.348 X 3 + e, where the brand image variable X 1 (0.792) service features X 2 (0.176) and promotion X 3 (0.348) so that the most dominant variable is brand image variable. The results of the calculation of the resulting t test are t count > t table where the brand image variable is X 1 (8,173 > 1,985) service features X 2 (2,143 > 1,985) promotions X 3 (3,949 > 1,985) so it can be concluded that brand image, service features, and promotions have a partial effect on purchasing decisions on the shopee marketplace. The results of the calculation of the F test produced are F count > F table (137.454 > 2.70) so it can be concluded that brand image, service features and promotions simultaneously influence purchasing decisions on the shopee marketplace.